2005
DOI: 10.2134/jeq2004.0261
|View full text |Cite
|
Sign up to set email alerts
|

Surface Runoff and Transport of Sulfonamide Antibiotics and Tracers on Manured Grassland

Abstract: Despite their common use in animal production the environmental fate of the veterinary sulfonamide antibiotics after excretion is only poorly understood. We performed irrigation experiments to investigate the transport of these substances with surface runoff on grassland. Liquid manure from pigs treated with sulfadimidine was spiked with sulfadiazine, sulfathiazole, the herbicide atrazine (2-chloro-4-ethylamino-6-isopropylamino-1,3,5-triazine), and the conservative tracer bromide and spread onto eight plots. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 23 publications
5
101
0
3
Order By: Relevance
“…The environmental behaviour of sulfa drugs is mainly characterised by the acidic nature of their sulfonamide group that may occur as anionic form under neutral/slightly basic pH conditions in soilwater system [14]. Some studies on the mobility of sulfonamides in soils demonstrated their attitude to be leached along the soil profile [15] because of the net negative charge always present on the surface of soil particles [16,17]. When the antibiotic administration takes place directly in water, for instance in the case of aquaculture treatment, soil depurative and filtering activity is by-passed and the sulfonamide effect on the environment is even worse [18].…”
Section: Introductionmentioning
confidence: 99%
“…The environmental behaviour of sulfa drugs is mainly characterised by the acidic nature of their sulfonamide group that may occur as anionic form under neutral/slightly basic pH conditions in soilwater system [14]. Some studies on the mobility of sulfonamides in soils demonstrated their attitude to be leached along the soil profile [15] because of the net negative charge always present on the surface of soil particles [16,17]. When the antibiotic administration takes place directly in water, for instance in the case of aquaculture treatment, soil depurative and filtering activity is by-passed and the sulfonamide effect on the environment is even worse [18].…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonamides, including sulfadiazine (SDZ), belong to one of the major groups of veterinary drugs and are mainly used in pigs (10). Sulfonamides are poorly adsorbed in the animal gut; consequently, they are excreted unchanged in urine and feces (1,12,16,26) and reach the soil ecosystem via manuring.…”
mentioning
confidence: 99%
“…Therefore, the significant positive correlation between TC and developed area indicated that human sources might be a major contributor of TC. Studies have suggested that antibiotics in soil can be released into surface water through overland flow (Burkhardt et al 2005;Kreuzig et al 2005;Kay et al 2005;Davis et al 2006;Kim et al 2010). In barren land, the antibiotics attached to soil particles were easily transported to the river because of the lack of vegetation cover (Jent et al 2013).…”
Section: Correlation With Land Use Typesmentioning
confidence: 99%